Icarus 2.0: Redditors’ perceptions of the International Olympic Committee’s organizational legitimacy during the 2022 Beijing Winter Games - Hill, Megan R.; Price, Katey A. (Frontiers in Communication, 2025)
News of Russian Olympic Committee (ROC) figure skater Kamila Valieva’s positive test for the banned substance trimetazidine broke during the 2022 Beijing Winter Olympics. At only 15-years-old, Valieva’s status as a minor at the time of the Games subjected her to different standards than her adult competitors. Despite this fact, the decision to allow her to continue to compete at the Games sent shockwaves through sport fan communities around the world, particularly those devoted to figure skating. This study thus sought to understand how fans of figure skating perceived and made sense of the Valieva scandal as it unfolded during the Games, with particular attention paid to how fans reacted to the main sport’s governing body of the Olympics, the International Olympic Committee (IOC). Fans’ real-time posts to the social media platform Reddit were analyzed through the lens of organizational legitimacy theory. Thematic analysis revealed that fans’ posts about the IOC were either neutral, legitimate, or illegitimate, with fans overwhelmingly viewing the IOC as an illegitimate organization due to corruption, downplaying the scandal, and ineffectiveness. Figure skating fans on Reddit demonstrated a clear lack of trust in the IOC to govern the Games in a way that would ensure clean, equitable competition and, as a result, fans expressed waning interest in following the sport any further.